MORAL AND SPIRITUAL DETERMINANTS OF WHISTLEBLOWING INTENTION AMONG ISLAMIC ACCOUNTING STUDENTS - Luluk Musfiroh; Dewi Rahmawati (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to examine the moral and spiritual determinants of whistleblowing intention among sharia accounting students by analyzing the roles of the bystander effect, individual morality, and religiosity. This study adopts a quantitative approach with an associative design, utilizing primary data gathered through Likert-scale questionnaires and examined using multiple linear regression analysis. The findings reveal that the bystander effect does not significantly affect whistleblowing intention, indicating that situational factors are no longer the main drivers of ethical decision-making. In contrast, individual morality and religiosity exert a positive and significant influence, with religiosity emerging as the most dominant factor. These findings highlight a paradigm shift from situational-driven behavior to value-driven behavior, where ethical decisions are more influenced by the internalization of moral values and spiritual awareness rather than social environmental pressures. In conclusion, whistleblowing intention is primarily shaped by internal values, emphasizing that strengthening morality and religiosity is essential in fostering the courage to report wrongdoing.